The Cost of Environmental Degradation : Case Studies from the Middle East and North Africa - Croitoru, Lelia; Sarraf, Maria (World Bank, 2012)
Environmental degradation is costly, to individuals, to societies, and to the environment. This book, edited by Lelia Croitoru and Maria Sarraf, makes these costs clear by examining a number of studies carried out over the past few years by the World Bank's Middle East and North Africa region. Even more important than estimating the monetary cost of environmental degradation (COED), however, are the clear guidance and policy implications derived from these findings. This volume presents a new approach to estimating the impacts of environmental degradation. In the past, when government officials asked researchers the simple question how large are the impacts of environmental degradation? The response was often an emphatic 'large!' a rather imprecise number. The strength of this work is that it actually quantifies in economic terms how large is 'large' and thereby gains the attention of decision makers and offers specific insights for improved policy making. Finally, this book demonstrates the benefits of doing a coordinated, regional COED analysis that builds on the country-level studies. This two-tiered approach produces important synergies, in terms of both the methodologies used and the lessons learned.